Digging into Archaeology A Brief OER Introduction to Archaeology with Activities - Paskey, Amanda Walcott; Cisneros, AnnMarie Beasley (Open textbook library., 2020)
This book is intended for use in a variety of introductory archaeology settings, such as in lectures and lab courses. This text can complement an existing traditional text or completely replace a standard text. It can be used for its activities or as a study resource. When we wrote this text, we designed the chapters to be brief, providing concise and to-the-point information. This book is not intended to replace lectures or direct instruction from an instructor; rather, it supports learning in a variety of settings and formats. The book can be printed in whole, read digitally, or used piecemeal in either format. However you use this text, we hope that you find it serves as an instructive learning tool and that you dig archaeology as much as we do!